3.8k views
3 votes
Given the system of equations.

{-4x+y = 3
{2x - y = 12
Which of the options represents the resulting equation after an equivalent expression for y ls substituted into the
second equation.
2x - (4 X+3) = 12
-4(4y+)+y=3
2 (4x+3) - y
-4x+4 x-3=3

User Wasabi Fan
by
4.7k points

1 Answer

2 votes

Answer:

A. 2x - (4x + 3) = 12

Explanation:

A. 2x - (4x + 3) = 12

B. -4(4y+)+y=3

C. 2 (4x+3) - y

D. -4x+4 x-3=3

Given equation:

-4x+y = 3. (1)

2x - y = 12. (2)

From (1)

y = 3 + 4x

Substitute y = 3 + 4x into (2)

2x - y = 12 (2)

2x - (3 + 4x) = 12

Or

2x - (4x + 3) = 12

2x - 4x - 3 = 12

- 2x = 12 + 3

- 2x = 15

x = 15/-2

x = -7.5

Substitute x = -7.5 into (1)

-4x+y = 3 (1)

-4(-7.5) + y = 3

30 + y = 3

y = 3 - 30

y = -27

User Clayton Gulick
by
4.7k points